2012
DOI: 10.1371/journal.pone.0029161
|View full text |Cite
|
Sign up to set email alerts
|

Interferon and Biologic Signatures in Dermatomyositis Skin: Specificity and Heterogeneity across Diseases

Abstract: BackgroundDermatomyositis (DM) is an autoimmune disease that mainly affects the skin, muscle, and lung. The pathogenesis of skin inflammation in DM is not well understood.Methodology and FindingsWe analyzed genome-wide expression data in DM skin and compared them to those from healthy controls. We observed a robust upregulation of interferon (IFN)-inducible genes in DM skin, as well as several other gene modules pertaining to inflammation, complement activation, and epidermal activation and differentiation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
124
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 37 publications
16
124
0
3
Order By: Relevance
“…The pathogenesis of skin inflammation in DM is less well characterized than in muscle. Gene microarray analysis demonstrated an IFN signature in DM skin, although this study did not assign this as being 'type I' or 'type II' [82]. An in-vitro study comparing muscle-and skin-derived T cells demonstrated differential cytokine production between the two tissue types.…”
Section: Skinmentioning
confidence: 62%
“…The pathogenesis of skin inflammation in DM is less well characterized than in muscle. Gene microarray analysis demonstrated an IFN signature in DM skin, although this study did not assign this as being 'type I' or 'type II' [82]. An in-vitro study comparing muscle-and skin-derived T cells demonstrated differential cytokine production between the two tissue types.…”
Section: Skinmentioning
confidence: 62%
“…Our observation that the immune response in vitiligo is T H 1-specific is consistent with a previous report (38), and may explain why targeted treatments for psoriasis, a prototypic T H 17-mediated disease, are ineffective for vitiligo (20–22). The identification of an IFNG -specific signature in vitiligo is in sharp contrast to other inflammatory skin diseases, including dermatomyositis, cutaneous lupus erythematosus, and lichen planus, which express an IFN signature that reflects both Type I ( IFNA/B ) and Type II ( IFNG ) interferons, with a predominance of Type I over Type II (39, 40). Consistent with our findings, other studies report increased expression of IFNG in vitiligo skin, however they did not measure the expression of downstream gene targets or their functional/biological significance (13, 25, 38).…”
Section: Discussionmentioning
confidence: 93%
“…Two proinflammatory cytokines implicated in the pathogenesis of DM and CLE are TNF-α and IFN-α (Baechler et al, 2003; Braunstein et al, 2012; Moran and Mastaglia, 2014; Wong et al, 2012). Our study compares the effectiveness of two antimalarial drugs, QC and HCQ, at suppressing secretion of TNF-α and IFN-α from the PBMCs of DM and CLE patients and control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Given that both TNF-α and IFN-α have been implicated in the pathogenesis of DM and CLE, expanding understanding of the differential effects of antimalarials on proinflammatory cytokines may offer insight into why therapeutic responses vary (Braunstein et al, 2012; Nabatian et al, 2012; Wenzel et al, 2005; Wong et al, 2012). We examined the PBMCs of DM and CLE patients to quantify the ability of QC to inhibit secretion of TNF-α and IFN-α versus HCQ and controls.…”
Section: Introductionmentioning
confidence: 99%